Fabrication and characterization of hydroxyapatite based cow bone polysulfone mixed matrix membrane. Issue 1 (April 2021) - Nor Suhaida Rasman, Siti; Riduan Jamalludin, Mohd; Najieha Kamarudin, Suraya; Khadijah Hubadillah, Siti; Arif Budiman Pauzan, Mohammad; Hafiz Dzarfan Othman, Mohd
Abstract: In this work, polysulfone (PSf)/hydroxyapatite (HAp) mixed matrix membrane were prepared were prepared by using phase inversion technique for ultrafiltration application. The prepared PSf/HAp mixed matrix membrane were characterized in term of morphological and physicochemical properties by using SEM, contact angle measurement, membrane tensile measurement and membrane porosity. Meanwhile the performance of PSf/HAp mixed matrix membrane was conducted in term of pure water flux (PWF) by using permeability machine. The surface morphology of the MMMs showed the increasing pore number and size as the concentration of HAp increase. The increment weight ratio of the HAp in PSf membrane enhanced the membrane water flux from 113.44 L/m 2 .h.bar to 228.13 L/m 2 .h.bar due to increased porosity of the membrane. Meanwhile, the strength of the membrane was increased from 3.82 MPa to 5.2 MPa as HAp increases from 0 to 1.0 wt.% and decreased to 2.49 MPa at 1.5 wt.% HAp. This study suggested that HAp is a promising candidate as additive that can improve PSf membrane performance.